2009
DOI: 10.1002/clen.200800212
|View full text |Cite
|
Sign up to set email alerts
|

Trout Farm Effluent Effects on Water Sediment Quality and Benthos

Abstract: Several water (dissolved oxygen, pH, ammonia-nitrogen, nitrite-nitrogen, nitratenitrogen, total phosphorus and orthophosphate) and sediment (organic matter, total nitrogen, organic carbon and phosphorus) quality parameters, as well as benthic macroinvertebrate communities were investigated monthly between May 2007 and November 2007 at a rainbow trout farm located on one of the sources of the Sakarya River in Central Anatolia. Water and sediment samples were collected from three stations, i. e., the inlet of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
(15 reference statements)
1
7
1
Order By: Relevance
“…One possible interpretation is that macroinvertebrates may experience larger variations of water conditions along the stream network than those through the overland paths. In both dispersal paths, we observed that COD and transparency were important environmental variables in structuring macroinvertebrates community structure, which was in accordance with previous studies [46][47][48]. This may indicate that COD is one of the most important pollutants in the Basin and has some direct or indirect effects on macroinvertebrates community.…”
Section: Relationship Between Macroinvertebrates and Environmentsupporting
confidence: 91%
“…One possible interpretation is that macroinvertebrates may experience larger variations of water conditions along the stream network than those through the overland paths. In both dispersal paths, we observed that COD and transparency were important environmental variables in structuring macroinvertebrates community structure, which was in accordance with previous studies [46][47][48]. This may indicate that COD is one of the most important pollutants in the Basin and has some direct or indirect effects on macroinvertebrates community.…”
Section: Relationship Between Macroinvertebrates and Environmentsupporting
confidence: 91%
“…(Table ). These values were considerably lower than data presented by Kirkagac, Pulatsu and Topcu (). Those authors stated that in sediments from a small culture of rainbow trout (30 t year −1 ), total nitrogen constituted ca.…”
Section: Resultscontrasting
confidence: 73%
“…2G ) found in the present study and a range of 0.06–0.58 mgP/L increase found in another study where three different rainbow trout farms were investigated during one year ( Boaventura et al, 1997 ). Some other studies observed some increase from rainbow trout farms inlets to outlets for NH 4 -N ( Caramel et al, 2014 ; Guilpart et al, 2012 ; Kırkağaç, Pulatsu & Topcu, 2009 ; Lalonde, Ernst & Garron, 2015 ), BOD 5 ( Teodorowicz, 2013 ), total nitrogen ( Caramel et al, 2014 ; Lalonde, Ernst & Garron, 2015 ), total phosphorus ( Caramel et al, 2014 ; Kırkağaç, Pulatsu & Topcu, 2009 ; Lalonde, Ernst & Garron, 2015 ) and PO 4 -P ( Caramel et al, 2014 ; Guilpart et al, 2012 ). Furthermore, a significant decrease was observed in the present study at fish farms outlet compared to inlets for both DO ( P value <0.001) and pH ( P value =0.001) showing, as expected, (i) a global oxygen consumption due to fish metabolism ( Boyd & Tucker, 1998 ), and (ii) a production of carbon dioxide by fish with the consequence of lower pH value at the outlets ( Boyd & Tucker, 1998 ).…”
Section: Resultsmentioning
confidence: 90%